The Innovative Potential of the Book Industry in the Region: Approaches, Problems, Prospects - A. S. Metelkov; E. A. Stepanov (Библиосфера, 2022)
On the background of the civilizational paradigm change, the analysis of the innovative industrial potential is one of the relevant areas of book culture study, which lies in the mainstream of interdisciplinary research. The purpose of this article is to identify the specifics of the innovative potential of the regional book industry within the real processes taking place in the regional book culture. The article provides an overview of theoretical approaches to the concept of “innovative potential of the subject”, these approaches are extrapolated to the field of the book industry, and the challenges facing the system of book publishing and book distribution during the transition to a new stage of development are considered. Special attention is paid to the characteristic features of the implementation of innovative potential in province, the possible options for the development of regional book culture in terms of existing or emerging innovative potential are outlined. Successful examples include projects implemented at the intersection of official and unofficial culture, taking into account social and communication transformations, the generation of niche publishing and focusing on small communities.